Ensino de geografia e formação dos professores das séries iniciais do ensino fundamental: das expectativas do Curso Normal Superior da Unimontes à realidade - Zuba, Janete Aparecida Gomes (2006)
This dissertation investigates the teaching of Geography in the formation of the Teachers of the initial series of basic education, egresses of the Normal Superior Course of The Universidade Estadual de Montes Claros Unimontes, in the period ranging from 2000 to 2002, and who work in the Municipal schools of the City of Montes Claros, aiming to understand the process of formation in relation to their practices developed in this discipline. It is a research of quant-qualitative nature. The student-teachers of the Normal Superior course were characterized by taking into account the graduate course of their formation and in service, also the bonds established between the professional place and the staff. The proposal of the course in study begins by the principle of the experience of the professor as base of the formation in service, to prepare a professional who is reflective and capable of contextualizing, effectively, theory and practice. The study revealed that the teachers of the Municipal Education Schools had looked for the Normal Superior Course as a professional improvement, and not only as result of the requirement of the Lei de Diretrizes e Bases da Educação Nacional LDBEN/96. However, the examination of their theoretic-methodological position showed unfamiliarity, on the part of the majority, of what can be considered important to teach in Geography, including the absence of the called cartographic alphabetization.